2019
DOI: 10.3389/fenvs.2019.00153
|View full text |Cite
|
Sign up to set email alerts
|

Testing Contrast Agents to Improve Micro Computerized Tomography (μCT) for Spatial Location of Organic Matter and Biological Material in Soil

Abstract: Soil carbon is essential for soil and ecosystem functioning. Its turnover and storage in soil are multifaceted processes that involve microbial activity in complex physical matrices. Biological litter, which include plants, animals, and microorganisms, is decomposed in soil stimulating soil biota (archaea, bacteria, fungi, protists, and animals) activity and yielding soil organic matter (SOM). Such decomposition processes are influenced by local physico-chemical characteristics including the spatial distributi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…While manual pin-pointing of the PMA stained POM was not impeded, automated POM extraction from the CT volume may still prove to be challenging due to the lack of image contrast between POM and mineral soil www.nature.com/scientificreports/ particles. Very recent work by Lammel et al 38 applied a machine learning segmentation tool in synchrotron-based soil CT volumes but experienced limited success. Piccoli et al 39 suggested that an operator-based ability for the selection of thresholds may still result in the most accurate segmentation of POM in soil.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…While manual pin-pointing of the PMA stained POM was not impeded, automated POM extraction from the CT volume may still prove to be challenging due to the lack of image contrast between POM and mineral soil www.nature.com/scientificreports/ particles. Very recent work by Lammel et al 38 applied a machine learning segmentation tool in synchrotron-based soil CT volumes but experienced limited success. Piccoli et al 39 suggested that an operator-based ability for the selection of thresholds may still result in the most accurate segmentation of POM in soil.…”
Section: Resultsmentioning
confidence: 99%
“…However, the K-edge of Mo is situated at 20 keV, an energy level at which most X-rays may be attenuated by the soil mineral fraction, thereby probably making a dual energy approach similar to that used for Os challenging for non-synchrotron scanners and probably also for synchrotrons. Very recently, Lammel et al 38 identified gaseous iodide (I 2 ) as a plausible candidate for selective staining of OM in soil for use with synchrotron scanners. However, they did not fully demonstrate www.nature.com/scientificreports/ its selectivity for OM versus silt and clay sized mineral particles, nor in X-ray µCT soil volumes obtained with non-synchrotron scanners.…”
Section: Performance Of Pma Compared To Gaseous Oso 4 Staining Inspementioning
confidence: 99%
“…To increase the contrast between the two organic materials, Lammel et al stained a whole sample with iodine (I 2 ), which mostly interacts with SOM instead of the fungi material. [ 39 ] Differential absorption edge tomography at the I 2 ‐K‐edge (33.2 keV) finally emphasized the SOM, see Figure c. This is rendered in cyan color in Figure 8d.…”
Section: Differential Absorption Edge Xctmentioning
confidence: 95%
“…A number of heavy metal stains have been tested in order to accentuate the contrast (Peth et al, 2014;Van Loo et al, 2014;Maenhout et al, 2021). So far, only osmium (Peth et al, 2014;Zheng et al, 2020;Maenhout et al, 2021) and iodine (Lammel et al, 2019) stains have proved to specifically stain organic matter (though Schlüter et al (2022) suggest that Osmium binds to some minerals), to provide a detectable staining and to diffuse through the soil matrix. Osmium was successfully used to map soil organic matter (Rawlins et al, 2016).…”
Section: Localisation Of Organic Matter In Soilmentioning
confidence: 99%